Molecular Design of Semiconducting Polymers for High-Performance Organic Electrochemical Transistors - Nielsen,CBN; Giovannitti,A; Sbircea,DTS; Bandiello,EB; Niazi,MN; Hanifi,DH; Sessolo,MS; Amassian,AA; Malliaras,GGM; Rivnay,JR; McCulloch,IM (Journal of the American Chemical Society, 2016)
The organic electrochemical transistor (OECT), capable of transducing small ionic fluxes into electronic signals in anaqueous environment, is an ideal device to utilize in bioelectronic applications. Currently, most OECTs are fabricated with commerciallyavailable conducting poly(3,4-ethylenedioxythiophene) (PEDOT)-based suspensions and are therefore operated in depletionmode. Here, we present a series of semiconducting polymers designed to elucidate important structure-property guidelines requiredfor accumulation mode OECT operation. We discuss key aspects relating to OECT performance such as ion and hole transport,electrochromic properties, operational voltage and stability. The demonstration of our molecular design strategy is the fabrication ofaccumulation mode OECTs that clearly outperform state-of-the-art PEDOT based devices, and show stability under aqueous operationwithout the need for formulation additives and cross-linkers.